Not All Profit Shifting Is Created Equal? An Analysis of Internal Debt - Zarko Kalamov (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper analyzes how internal debt financing of multinational firms affects high-tax countries. It uses a dynamic small open economy model and takes into account that internal debt impacts both the multinational firms' investment decisions and the government's tax policy. The government has incentives to redistribute income from firm owners to workers. If the government's redistributive motive is not too strong, internal debt reduces welfare in the short term by decreasing tax revenues. However, debt financing stimulates capital accumulation and exerts a positive long term welfare impact. If the multinational firm additionally manipulates transfer prices, the adverse short term welfare effects may extend to the long term.
Keywords: F23; H25; H70; 330; internal debt; profit shifting; tax havens